ANALISIS HUBUNGAN ANTARA PENDAPATAN BADAN USAHA MILIK DAERAH DENGAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH PEMERINTAH KOTA MAGELANG PERIODE 2008 – 2017 - Aodra Sanjaya; Lorentino Togar Laut; Whinarko Juliprijanto (Universitas Tidar, 2020)
he purpose of this research was to describe and analyze the relationship betweenRegional Owned Enterprise Revenue and Regional Income And Expenditure Budget ofMagelang arround 2008 – 2017. The data that used in this research was secondary data andwas collected from The Central Bureau of Statistic of Magelang. The analysis method thatused was linear regression. The result of linear regression showed that the coefficient ofRegional Owned Enterprise Revenue was 5,765 and = 9,269 > = 2,306, so the zerohypothesis ( ) was rejected and the alternative hypothesis ( ) was accepted. The conclutionof this research was Regional Owned Enterprise Revenue and Regional Income AndExpenditure Budget had significant relationship, Regional Owned Enterprise Revenueinfluenced to Regional Income And Expenditure Budget.